3
$\begingroup$

enter image description here

I am confused in showing that the sequence is exact at $A_{n-1}' \oplus B_{n-1}$. Here is part of my argument.

Note that $(\rho_4+f_5)\circ (f_4,-\delta_4)=\rho_4 \circ f_4-f_5 \circ \delta_4=0$ by commutativity of the diagram. This shows that $\text{im}(f_4,-\delta_4) \subset \text{ker}(\rho_4+f_5)$. Conversely, let $(a',b) \in \text{ker}(\rho_4+f_5)$. Then $\rho_4(a')+f_5(b)=0 \implies f_5(b)=-\rho_4(a')$.

I have no idea how to proceed. Can someone give me some hint? Thanks!

$\endgroup$
4
$\begingroup$

It's too awkward to keep track of the subscripts on the morphisms, so I'll write all $\delta_j$ as $\delta$ etc. I also assume that each $f:C_k\to C'_k$ is an isomorphism, so in particular, $f:C_{n-1}\to C'_{n-1}$ is an isomorphism.

You have $f(b)=-\rho(a')$. Then $$0=-\rho(\rho(a'))=-\rho(f(a'))=f(\delta(b)).$$ As $f:C_{n-1}\to C'_{n-1}$ is an isomorphism, $\delta(b)=0$ and by exactness, $b=-\delta(a^*)$ where $a^*\in A_{n-1}$. Then $$\rho(f(a^*)-a')=\rho(f(a^*))-\rho(a')=f(\delta(a^*)+b)=0$$ so $a^*-a'=\rho(c')$ by exactness. Then $c'=f(c^*)$ since $f:C_n\to C_n'$ is an isomorphism, and $a^*-a'=f(\delta(c))$. I would try $-\delta(c)+a^*$ as a candidate for an element of $A_{n-1}$ mapped to $(a',b)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.